This study entitled “Analisis Faktor Produksi Usahatani Padi Rojolele dan Padi IR64 (Case Study : Desa Candirejo, Kecamatan Ngawen, Kabupaten Klaten, Jawa Tengah)”. This study aims to determine the difference income between Padi Rojolole and Padi IR64’s f - Sylvianingrum Firdauzi; Edy Yusuf Agung Gunanto (Diponegoro Journal of Economics, 2013)
This study entitled “Analisis Faktor Produksi Usahatani Padi Rojolele dan Padi IR64 (Case Study : Desa Candirejo, Kecamatan Ngawen, Kabupaten Klaten, Jawa Tengah)”. This study aims to determine the difference income between Padi Rojolole and Padi IR64’s farmers, and also to find level of efficiency in using production factors. Multiple linear regression, analysis of the frontier, and the efficiency test are used to analyzing the study. Multiple linear regression analysis using dependent variable number of production and independent variable include land, seeds, fertilizers, pesticides, and amount of labor. Based on data analysis obtained a result that all variables have positive and significantly affect in Padi Rojolele and Padi IR64 production. Technical efficiency value of Padi Rojolele and Padi IR64 farmers are same that is 0,99999895, thus rice farming is technically inefficient. The efficiency value Padi Rojolele farmers is about 2,6939494 and value economic efficiency is about 2,6939466, thus Padi Rojolele rice farming is not efficient and economically priced yet. The value of price efficiency in Padi IR64 rice farming is 1,420384 and the value of economic efficiency is 1,420383, thus Padi IR64 rice farming inefficient and economical price yet. This study is also found ratio of R/C Padi Rojolele rice farming are 6,28, while Padi IR64 are 2,47. It is shows that Padi Rojolele rice farming in study area is more profitable than IR64 rice farming.